Peran Kader Posyandu dalam Penurunan Angka Stunting - Ria Nur Faizah; Iraini Ismail; Netty Dyah Kurniasari (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Posyandu cadres have a role as the main movers of all activities carried out at the posyandu. The existence of important and strategic cadres, when the services provided receive sympathy from the community, will have positive implications for community awareness and participation. Stunting is one of the national development problems in Indonesia which can hamper economic growth, increase poverty and inequality. This research aims to determine the role of posyandu cadres in dealing with stunting in Pesanggrahan Village, Kwanyar District, Bangkalan Regency. The type of research used is descriptive qualitative. Using the case study method (case studies). The data collection technique for this research is using in-depth interviews, observation, documentation. To determine the informants, what was done was to determine the target population elements that were thought to be most suitable for collecting data, including posyandu cadres, family planning cadres and village midwives. Based on e-PPGBM data, the prevalence of stunting in 2022 will reach 85 toddlers spread across 16 villages. The Pesanggrahan village of Kacatan Kwanyar is one of the villages with a relatively high stunting rate compared to other villages, namely reaching 10 children under five in 2022. From the research results, posyandu cadres have carried out their duties and roles optimally. This is proven by the very drastic reduction in stunting rates in a relatively fast period, namely from 10 in 2022 down to 2 in 2023.